REVIEW PAPER Cardiovascular mortality in rheumatoid arthritis patients - Olas, Jacek; Gajos, Grzegorz; Bucka, Jolanta; Włoch, Alicja; Dworak, Agata; Kolasa, Renata; Samborski, Włodzimierz (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2006)
Rheumatoid Arthritis (RA) is a chronic inflammatory disease of joints that affects also cardiovascular system. As a consequence of it, coronary artery disease (CAD) and heart failure (HF) with cardiac deaths, appear more than double comparing to the general population. Vascular endothelial dysfunction with accelerated atherosclerotic process, imbalance in the autonomic nervous system, and delay in the process of diagnosis and management are found among reasons leading to increased mortality of RA patients. It was observed that RA patients may develop CAD and HF even on early stages of the disease, regardless of lack of traditional cardiovascular risk factors and with absence of angina symptoms. Accordingly, there is a need for reliable and simple screening test addressed for asymptomatic patients from group of high risk of cardiovascular disease. Identifying high risk patients with Systemic Coronary Risk Evaluation (SCORE), basic additional findings and assessment of cardiac markers (CRP, BNP), should be done in every case of clinical evaluation of RA patient.